Repeatability of corneal curvature with the MS-39 anterior segment tomographer in a cataractous population - Achim Langenbucher; Nóra Szentmáry; Alan Cayless; Muntadher Al Karam; Theo G. Seiler; Jascha Wendelstein (PLoS ONE, 2025)
Purpose The purpose of this study was to investigate the repeatability of optical coherence tomography in measuring radius of curvature (ROC) and asphericity (Q) of corneal epithelium, stroma and endothelium in a large patient cohort. Methods In this retrospective non-randomized cross sectional single-center study we evaluated a dataset containing 600 anterior segment optical coherence tomography measurements from 200 eyes (3 repeat measurements each) taken prior to cataract surgery. Measurements were exported containing height map data for the epithelium, stroma and endothelium surface. Model surfaces (floating sphere in a 3 (BFS3) and 6 mm zone (BFS6) and conic surface in a 3 (Conoid3) and 6 mm zone (Conoid6)) were fitted using nonlinear iterative optimization minimizing the height difference between measurement and model. The mean (MEAN) and standard deviations (SD) for each sequence of measurements were derived and analyzed. Results MEAN ROC for epithelium was 7.68/7.72/7.67/7.67 mm with BFS3/BFS6/Conoid3/Conoid6 and Q was −0.16/-0.19 with Conoid3/Conoid6. Corresponding values for stroma were 7.62/7.64/7.55/7.58 mm and −0.38/-0.24, and for endothelium they were 6.43/6.49/6.40/6.37 mm and −0.29/-0.33. Variations of the 3 repeat measurement ranged between 7–19/18–31/21–32 micron for epithelium/stroma/endothelium, and variation in Q was 0.14/0.20/0.14 with Conoid3 and 0.03/0.05/0.06 with Conoid6. Conclusions Fitting floating sphere or conoid model surfaces to the map data seems to be a very robust and reliable method for extracting ROC and asphericity from all data within a region of interest. For extraction of asphericity, the 6 mm zone should be used due to fewer variations.